Recurrent Aortic Dissection: Observations From the International Registry of Aortic Dissection. Issue 14 (4th October 2016) - Isselbacher, Eric M.; Bonaca, Marc P.; Di Eusanio, Marco; Froehlich, James; Bassone, Eduardo; Sechtem, Udo; Pyeritz, Reed; Patel, Himanshu; Khoynezhad, Ali; Eckstein, Hans-Henning; Jondeau, Guillaume; Ramponi, Fabio; et al.
Abstract : Background: Improved medical care after initial aortic dissection (AD) has led to increased survivorship and a population of individuals at risk for further cardiovascular events, including recurrent AD. Reports describing recurrent ADs have been restricted to small numbers of patients from single institutions. We used the IRAD (International Registry of Acute Aortic Dissection) database to examine the clinical profiles and outcomes of patients with recurrent AD. Methods: We identified 204 patients enrolled in IRAD with recurrent AD. For the primary analysis, patient characteristics, interventions, and outcomes were analyzed and compared with 3624 patients with initial AD. Iterative logistic modeling was performed to investigate variables associated with recurrent AD. Cox regression analyses were used to determine variables associated with 5-year survival. A subset of recurrent AD patients was analyzed for anatomic and demographic details of initial and recurrent ADs. Results: Patients with recurrent AD were more likely to have Marfan syndrome (21.5% versus 3.1%; P <0.001) but not bicuspid aortic valve (3.6% versus 3.2%; P =0.77). Descending aortic dimensions were greater in patients with recurrent AD than in patients with initial AD independently of sentinel dissection type (type A: 4.3 cm [3.5–5.6 cm] versus 3.3 cm [2.9–3.7 cm], P <0.001; type B: 5.0 cm [3.9–6.0 cm] versus 4.0 cm [3.5–4.8 cm], P <0.001), and this observation was accentuated among patients with Marfan syndrome. In multivariate analysis, the diagnosis of Marfan syndrome independently predicted recurrent AD (hazard ratio, 8.6; 95% confidence interval, 5.8–12.8; P <0.001). Patients with recurrent AD who presented with proximal followed by distal AD were younger than patients who experienced distal followed by proximal dissection AD (42.1±16.1 versus 54.3±14.8 years; P =0.004). Conclusions: Among those suffering acute aortic dissection, 5% have a history of a prior aortic dissection. Recurrent AD is strongly associated with Marfan syndrome. Abstract : Supplemental Digital Content is available in the text.